Indonesian Constitutional Court’s Moral Legitimacy: A Dworkinian Rights-Based Defense - Kurnia, Titon Slamet; Darumurti, Krishna D.; Moonik, Prisilia Kornelia (Faculty of Law, Universitas Padjadjaran, 2025)
This study discusses the moral legitimacy of constitutional adjudication in general, with a particular focus on the Indonesian Constitutional Court. Moral legitimacy is crucial as it justifies the necessity of Constitutional Court—not merely because of its existence is stipulated by the 1945 Constitution. This issue is also discussed in response to the legislature’s (the People’s Representative Council) adverse reactions to the Constitutional Court, including efforts to weaken its authority. Additionally, moral legitimacy is also related to the well-known critique of constitutional adjudication: the counter-majoritarian difficulty. This study draws on Ronald Dworkin Rights-Based Theory, which defends constitutional adjudication as a means of safeguarding individual rights. Accordingly, the moral legitimacy of the Constitutional Court is framed as Dworkinian Rights-Based Judicial Review. From this perspective, constitutional adjudication serves as a shield for minorities against the dangers of majoritarian democracy and the tyranny of the majority. The Constitutional Court is therefore indispensable, as it upholds individual rights against legislative power, based on the principle of equal concern and respect.